Autoradiographic localization of tryptamine binding sites in the rat and dog central nervous system - McCormack, JK (J Neurosci, 1986)
Tryptamine, an endogenous trace amine, is currently postulated to be a neuromodulator or neurotransmitter in the mammalian CNS. High-affinity binding sites have been described for tryptamine in rat brain homogenate preparations. The present study further characterizes tryptamine binding throughout the CNS and delineates its distribution using in vitro receptor binding in conjunction with autoradiographic techniques. Saturation studies on 20-micron-thick brain sections suggest a single class of binding sites (Hill coefficient = 0.97 +/- 0.04) with a high affinity (KD = 4.79 +/- 1.55 nM). In competition studies, kynuramine and tetrahydrobetacarboline significantly inhibited H3-tryptamine binding while serotonin, dopamine, and phenylethylamine failed to significantly inhibit it. The most potent inhibitor of H3- tryptamine binding was tryptamine (KI = 4.19 +/- 2.13 nM). In rat brain sections processed for in vitro autoradiography, highest binding occurred in the following limbic structures: the accumbens nucleus, the amygdalohippocampal area, the lateral septal nucleus, the entorhinal cortex, and the anterior olfactory nucleus. At diencephalic levels, the highest binding was observed in the reuniens thalamic nucleus, the paraventricular thalamic nucleus, the medial habenular nucleus, the central medial thalamic nucleus, and the arcuate hypothalamic nucleus. In the midbrain of the rat, binding was most notable in the interpeduncular nucleus, the superficial layer of the superior colliculus, the periaqueductal gray, and the paranigral nucleus. In the lower brain stem of the dog, binding was evident in the external cuneate nucleus, the spinal trigeminal nucleus, and in the region of the solitary nucleus. Binding was also present in both the ventral and dorsal horns of the canine spinal cord.(ABSTRACT TRUNCATED AT 250 WORDS)